Give me the future [compact disc] - Ahmed, Riz, 1982-; BIM (Republic, 2022)
Give Me The Future, Bastille's wildly-ambitious new album is a tribute to tech times and a glimpse of what could be to come. Exploring both the opportunities of new technology and the dark side of lives lived online, it's as playful as it is thought-provoking, as dystopian as it is dancefloor-friendly and as electronic as Bastille have ever been. Executive produced by Ryan Tedder.